"Only English Counts": the impact of English hegemony on South-Korean athletes. Issue 3 (29th July 2019) - Brown, Clara Lee; Ward, Natalia; Nam, Benjamin H.
Abstract : Purpose: While conceived to examine key factors affecting post-retirement career advancement of retired elite athletes in South Korea, the purpose of this paper is to report how English, as a de facto global lingua franca, functions as a powerful gatekeeper in the sports administration field. Design/methodology/approach: Interpreted through the lens of Bourdieu's linguistic capital and Gramsci's hegemony of language, the present study draws on content analysis of semi-structured individual interviews, as well as focus group interviews, conducted with thirty former South Korean elite athletes. Findings: Based on the data analysis, systematic bias toward athletes was uncovered, privileging English as the single determining factor for employment. Furthermore, the educational implications for adult learners of English as a Foreign or English an Additional Language reveal unrealistic expectations of top–down language policies. Originality/value: Perspectives of athlete participants, an underrepresented group in educational research, within the South Korean globalization context shed critical light on the pervasive aspects of English hegemony and its unexamined dimensions.